2010
DOI: 10.2298/vsp1006487j
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cerebral-umbilical Doppler ratio in prediction of fetal distress in patients with preeclampsia

Abstract: The C/U ratio values obtained from spectral Doppler analysis in fetal vessels showed a highly significant correlation with fetal pH at birth in the patients with preeclampsia. The results of our study confirmed the reliability of C/U ratio in estimation of fetal condition in preeclamptic patients. Very low C/U ratio values in patients with preeclampsia indicate that in these fetuses fetal acidosis and fetal distress may be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Jurisic et al [9] concluded that the reliability of C/U ratio in the estimation of fetal condition in preeclamptic patients is high. Very low C/U ratio values in patients with preeclampsia indicate that in these fetuses, fetal acidosis and fetal distress may be expected.…”
Section: Middle Cerebral Artery Doppler Waveformmentioning
confidence: 99%
“…Jurisic et al [9] concluded that the reliability of C/U ratio in the estimation of fetal condition in preeclamptic patients is high. Very low C/U ratio values in patients with preeclampsia indicate that in these fetuses, fetal acidosis and fetal distress may be expected.…”
Section: Middle Cerebral Artery Doppler Waveformmentioning
confidence: 99%
“…Jurisic et al 19 concluded that the reliability of CPR ratio in the estimation of foetal condition in preeclamptic patients is high. Very low CPR ratio values in patients with preeclampsia indicate that in these foetuses, foetal acidosis and foetal distress may be expected.…”
Section: Performance Characteristics Of Doppler Indicesmentioning
confidence: 99%